PERUBAHAN STATUS HUBUNGAN KERJA DARI PKWT MENJADI PKWTT PADA PT ANGKASA PURA SUPPORT BERDASARKAN UNDANG-UNDANG KETENAGAKERJAAN - Muluk, Adika Try; Wijiningsih, Ninuk (Tribuere, 2024)
The employment relationship between workers and companies is a crucial aspect of labor law in Indonesia. One of the recurring issues is the misuse of Fixed-Term Employment Agreements (PKWT) by companies to avoid obligations in granting Permanent Employment Agreements (PKWTT). This study focuses on the case of PT Angkasa Pura Support, which was the subject of Supreme Court Decision No. 20/Pdt.Sus-PHI/2022/PN.Kpg, where a worker who had been employed for more than seven years remained on a contract status, violating Article 59 of Law No. 13 of 2003 on Manpower. This research applies the Theory of Legal Protection and Legal Certainty to analyze this phenomenon. The study adopts a normative juridical method, reviewing legal regulations, legal doctrines, and case studies on court decisions. The findings indicates many companies do not register PKWT contracts with the Ministry of Manpower, leading to weak supervision and enabling companies to maintain workers under contract status unlawfully. The conclusion emphasizes that the Supreme Court’s decision sets an important legal precedent in protecting workers’ rights. Therefore, the government must strengthen its monitoring mechanisms to ensure the proper implementation of labor regulations.